DEVELOPING TOUR PACKAGE PRICE SYSTEM IN TRAVEL BUREAU COMPANIES - Jeni Susanti; I G. M. Karma (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2019)
Travel bureau is a service company that provides sales and service of travel related products from various suppliers, such as hotels, restaurants, transport and so forth. The product is packed in a tour package and is offered to tourists or agents, for a certain price. The diversity of wishes of potential customers as well as the efforts to attract larger prospective customers, the company is eager to create a system that can provide broad flexibility for companies and prospective customers to choose and arrange their own package tour. The system is expected to set the price of the package quickly and in accordance with company policy. This research resulted in a system developed with object-oriented methodology and using the programming language VB.Net 2012 and MySQL as its database. This system gives the user the freedom to choose and arrange their own tour package as they wishes and the system will set the price of the product according to the applicable policy. The pricing policy includes the country of origin, the number of persons and the service time associated with the high/peak season period. The system can also present the price of the package in various currencies.